A new criterion of interfacial fracture of particle/polymer composites. (1st January 2013) - Ma, Bo; Chen, Jian-kang
The fracture of interface between particles and polymeric matrix is one of the dominant mechanisms leading to the failure of particulate-reinforced composites. Owing to viscosity in polymeric matrix, the interfacial fracture is controlled by the local strain at interface. In this paper, the interfacial fracture of an elastic spherical particle embedded in an infinite visco-elastic matrix is analysed based on the principle of energy. Calculation is carried out on the work done by external loads, and the variation of strain energy of matrix and the particle, as well as the surface energy just before and just after interfacial fracture, and then a new interfacial strength model is proposed in terms of local critical strain. The effects of particle size and relaxation time of matrix on the critical strain during interfacial fracture are numerically discussed. From the new model we find that the critical strain significantly depends on the modulus, and Poisson's ratio of matrix and particle as well as the relaxation time of matrix. It is also found that the critical strain possess remarkable size effect.